NEURAL NETWORK SYSTEM IDENTIFICATION: EXPERIMENTAL APPROACH OF A QUARTER CAR MODELLING - Dirman Hanafi Burhannuddin (Penerbit UTHM, 2012)
This book is intended for senior undergraduate or post graduate in control system engineering. This book is based on the author research and study experiences. This book covers topics on neural network, car suspension system, vibration dynamic model, experimental method and system identification. It is aimed to give overview a quarter car modelling using intelligent system identification. This book is organized in 6 chapters.